National Golf Academy to be set up - Par, Golf (Par Golf, 2012)
The Malaysian Golf Association (MGA) together with Universiti Utara Malaysia (UUM) are working in collaboration to set up the National Golf Academy (NGA) with provides golfers with an avenue to pursue formal studies once they are finished with secondary school.